Behavior of embankments on new Liskeard varved clay / Suzanne M. Lacasse, Charles C. Ladd. - Massachusetts Institute of Technology. Department of Civil Engineering.; Ladd, Charles C. (Charles Cushing); Massachusetts. Department of Public Works.; United States. Federal Highway Administration.; Lacasse, Suzanne M. (Tufts University. Tisch Library., 2019)
1 online resource (270 leaves) : illustrations.; "Prepared for Commonwealth of Massachusetts Department of Public Works in cooperation with U.S. Dept. of Transportation Federal Highway Administration."; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.